Poor Compliance with ACG Guidelines for Nutrition and Antibiotics in the Management of Acute Pancreatitis: A North American Survey of Gastrointestinal Specialists and Primary Care Physicians - Sun, Edward; Tharakan, Mathew; Kapoor, Sumit; Chakravarty, Rajarshi; Salhab, Aladin; Buscaglia, Jonathan M; Nagula, Satish (JOP. Journal of the Pancreas, 2013)
Context Despite recent updates in the treatment of acute pancreatitis emphasizing enteral nutrition over parenteral nutrition as well as minimizing antibiotic usage, mortality rates from acute pancreatitis have not improved. Data has been limited regarding physician compliance to these guidelines in the United States. Methods A 20 question survey regarding practice patterns in the management of acute pancreatitis was distributed to physicians at multiple internal medicine and gastroenterology conferences in North America between 2009 and 2010. Responses were analyzed using the chi-square test and multivariate logistic regression. Results Out of 406 available respondents, 43.3% of physicians utilize total parenteral nutrition/peripheral parenteral nutrition (TPN/PPN) and 36.5% utilize nasojejunal (NJ) feedings. The preferred route of nutrition was significantly related to practice type (P<0.001): academic physicians were more likely to use NJ tube feeding than private practice physicians (52.1% vs. 19.9%) while private practitioners were more likely to utilize TPN/PPN than academic physicians (70.2% vs. 20.5%). Gastroenterologists and primary care physicians were equally non-compliant as both groups favored parenteral nutrition. Multivariate logistic regression demonstrated that practice type (P<0.001) was the only independent predictor of route of nutrition. Most survey respondents appropriately do not routinely utilize antibiotics for acute pancreatitis, but when antibiotics are initiated, they are for inappropriate indications such as fever and infection prophylaxis. Conclusions Many North American physicians are noncompliant with current ACG practice guidelines for the use of artificial nutrition in the management of acute pancreatitis, with overuse of TPN/PPN and underutilization of jejunal feedings. Antibiotics are initiated in acute pancreatitis for inappropriate indications, although there are conflicting recommendations for antibiotics in severe acute pancreatitis. Improved compliance with guidelines is needed to improve patient outcomes. Image: The most common reasons cited for using parenteral nutrition.